EVALUASI KEBIJAKAN JAMINAN PERSALINAN DI PROVINSI DAERAH ISTIMEWA YOGYAKARTA TAHUN 2012 - Ummul Khair (Center for Health Policy and Management, 2013)
Background: The Ministry of Health made a breakthroughthrough delivery care scheme as one solution to reducing theMMR and IMR called Jampersal. This policy is a deliveryassurance scheme intended for all pregnant women and newmothers in Indonesia who are not covered by any insuranceyet. Delivery care assurance scheme consist prenatal care,postnatal care including family planning postpartum andnewborn care. This program also applied in the special regionof Yogyakarta as one of the program in improving the health ofmothers and children. During the implementation in Yogyakarta,the program still has some obstacles.Objective: This study aimed to evaluate the delivery careassurance policy in the province of Yogyakarta.Methods: The research design used case study design. Theresearch was conducted in the province of Yogyakarta. whichThe sampling technique used was stratified sampling. The unitof analysis in this study is the health districts / municipalities,general hospitals, health centers and private practice midwiveswho administer Jampersal. Data collected by in-depthinterviews.Results: The result of this research shows that there aremany problems in terms of input, process and output. In termsof input, the problems are related to human resources, financial,means and policy. In terms of process, the problems are relatedto socialization, regulations of patient, process of claiming,referral system and funding. In terms of output, the problem isrelated to overcrowding, patient refusal, and complains fromthe consumer.Conclusion: This program is a good program for reduction ofinfant and maternal mortality rates, but still needs someimprovement. Improvements are needed in terms ofstrengthening cross-sector coordination, socialization of theprogram should be optimized, stregthening the electronic-basedreferral system, strengthening the commitment and motivationof personnel and improvement of health infrastructures.Keywords: Delivery Care Assurance Policy, Policy Evaluation.